HISTORICAL PERSPECTIVE TAKING AND THE SELF IN ONLINE COMMUNITY DISCUSSIONS. Issue 7 (9th August 2022) - Matthews, Jolie C.
ABSTRACT: This article investigates how members of an online community engaged in historical perspective taking in their discussions of the events and figures portrayed in a historical television show. As a means to justify their interpretations and situate themselves inside the possible mindsets of historical figures, members drew on three aspects of the "self" in their practices: the experience-self, the identity-self, and the abstract-self . Members challenged one another's views and provided counterarguments to support challenges to their perspectives, while simultaneously failing to acknowledge the problematic elements sometimes inherent in their views. This article extends the literature on perspective taking, content analysis, and historical interpretation in community discussions.